THE EFFECT OF PRODUCT QUALITY TOWARD INTEREST IN BUYING UMKM PRODUCTS IN TASIKMALAYA CITY - Suci Putri Lestari; Kusuma Agdhi R (Politeknik Negeri Semarang, 2019)
UMKM represent business activities that can expand employment and reduce problems while also providing economic services to the community and can facilitate the process of equity and increase public budgets, encourage economic growth, and enhance national success. This study aimed to look at differences in product quality towards the buying interest of UMKM products in Tasikmalaya. And to know the purpose of increasing consumer buying interest. Research uses explanatory research methods. Use this method because research not only discusses empirical facts found in the field, but also discusses and explains the relationship between indicators. Using the sampling method by opposing questionnaires to 120 residents of Tasikmalaya who know about UMKM information in Tasikmalaya. The object of research is UMKM in the City of Tasikmalaya. The research subjects are consumers of UMKM products. Analysis using regression with the results of product quality affect the buying interest of UMKM products in the city of Tasikmalaya